1993
DOI: 10.1021/jo00072a008
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitized electron transfer from azoalkanes: generation, fragmentation, and rearrangement of radical cations structurally related to dicyclopentadiene

Abstract: The azoalkanes la-c extrude nitrogen upon photosensitized electron transfer (PET) to yield 1,3radical cation intermediates 2,+, which undergo interesting transformations. Electron back transfer (BET) affords the unrearranged housanes 2, but significant rearrangement to dicyclopentadiene derivatives 3 occurs prior to BET. In some cases, fragmentation to cyclopentadienes 4 is observed, a cycloreversion that occurs at the 1,3-radial cation stage rather than through the corresponding 1,3-biradical intermediates. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…129,130 Addition of biphenyl as a redox mediator results in an increase in the rate of reaction and also changes the distribution of products. The authors proposed that BET from DCA •− to 71 •+ leads to 1,3-diradical 71 , which can rapidly form housane 67 .…”
Section: Photoinduced Electron Transfermentioning
confidence: 99%
See 1 more Smart Citation
“…129,130 Addition of biphenyl as a redox mediator results in an increase in the rate of reaction and also changes the distribution of products. The authors proposed that BET from DCA •− to 71 •+ leads to 1,3-diradical 71 , which can rapidly form housane 67 .…”
Section: Photoinduced Electron Transfermentioning
confidence: 99%
“…Adam and Sendelbach demonstrated that photooxidation of azoalkane 66 led to extrusion of dinitrogen, followed by ring closure to housane 67 , rearrangement to cyclopentene 68 , or intramolecular trapping of the pendant alcohol to produce spiroethers 69 and 70 (Scheme ). , Addition of biphenyl as a redox mediator results in an increase in the rate of reaction and also changes the distribution of products. The authors proposed that BET from DCA •– to 71 •+ leads to 1,3-diradical 71 , which can rapidly form housane 67 .…”
Section: Photoinduced Electron Transfermentioning
confidence: 99%
“…One of these is fragmentation (path E), which is detailed in Scheme 10 for the norbornene-annelated derivative; in fact, cycloreversion into the two cyclopentadienes dominates over the diastereoselective 1,2-methyl migration. 8,27 The mechanistic reasons for this reactivity preference are yet to be elucidated, but presumably the rigidity of the annelated bicyclic ring encumbers the proper conformational alignment for the methyl shift (cf. the twisted conformation in Fig.…”
Section: Perspectivesmentioning
confidence: 99%
“…7 In the case of norbornadiene annelation, fragmentation to cyclopentadienes competes with the 1,2-shift (path E). 8 The chemical reactivity of cyclopropane radical cations, the parent structures for the more strained cyclopentane-1,3-diyl radical cations, has been extensively explored in recent years. [9][10][11][12][13][14][15][16][17] The rich array of chemical transformations for cyclopropane radical cations are particularly well manifested for the strained cyclopentane-1,3-diyl derivatives (Scheme 1), which are the subject of the present review.…”
Section: Introductionmentioning
confidence: 99%
“…We have studied the photoreactions of trans -1- o -hydroxyphenyl-2-phenylcyclopropane, trans - 1 , a trans -1,2-diarylcyclopropane bearing a hydroxyl function in one ortho position. This substrate was of interest because its excited singlet state may react by (excited state) proton transfer (ESPT) , to the cyclopropane moiety, whereas its radical cation may react by intramolecular nucleophilic capture, aside from the wealth of other reactions suggested by the analogy to previous studies.…”
Section: Introductionmentioning
confidence: 99%